Ascorbic acid treatment of bread flour - Siochi, Ma. Noela S.
The performance of ascorbic as a flour improver was evaluated in this study. The first phase focused on determining the optimum level of ascorbic acid incorporation. Three levels. 0.0015%, 0.0020%, and 0.0025%, were tested in three baking trials. All these levels registered significant positive effects on loaf volume, specific volume and many sensory attributes of the baked breads. Statistical analysis showed that the effects of the three different levels tested were not significantly different from each other. The 0.0020% level, however, gave a slightly better result in terms of loaf volume and specific volume. It also received better mean ratings in a number of sensory attributes evaluated by the panelists. The second phase of the study compared the performance of ascorbic acid as flour improver with the widely used KBro3 Levels of incorporation were 0.0020% for the former and 0.0025% for the latter. Ascorbic acid treated flour gave less compact breads. Subjective tests gave results which were in favor of loaves from ascorbic acid treated flour. The rate of staling of loaves from untreated and ascorbic acid treated flour over an 8-day storage period was comparable. Difference in treatment did not significantly affect the compressionability of the breads at any point in the storage time. Panelists' ratings on sensory attributes tend to approximate the shelf life of both breads to 4 days.